A novel FeNi-based bulk metallic glass with high notch toughness over 70 MPa m1/2 combined with excellent soft magnetic properties. (June 2020) - Zhou, Jing; Wang, Qianqian; Hui, Xidong; Zeng, Qiaoshi; Xiong, Yuwei; Yin, Kuibo; Sun, Baoan; Sun, Litao; Stoica, Mihai; Wang, Weihua; Shen, Baolong
Abstract: A novel Fe39 Ni39 B12.82 Si2.75 Nb2.3 P4.13 bulk metallic glass (BMG) with high notch toughness of 72.3 MPa m 1/2, large plastic strain of 9.8%, high yield strength of 2930 MPa, and a large critical diameter of 2.5 mm was successfully developed. This BMG also exhibits excellent soft magnetic properties, i.e., higher saturation magnetic flux density of 0.86 T, extremely low coercivity of 0.65 A/m, and high effective permeability of 23, 250 with high frequency stability. Its toughness value is the highest among Fe-based BMG family. The origin of high toughness was also investigated in detail by using synchrotron X-ray diffraction and aberration-corrected high-resolution transmission electron microscopy. It was found that the high toughness are attributed to atomic-scale structural heterogeneity that resulted from large free volume, high content of metal-metal bonds and high structural disorder degree, which can promote the multiple shear bands and hinder the subsequently propagation. This work provides useful guidelines for developing tough FeNi-based BMGs with high strength and excellent soft magnetic properties from an atomic structural perspective. Graphical abstract: Unlabelled Image Highlights: FeNiBSiNbP bulk metallic glass with high notch toughness and strength was developed. This FeNi-based metallic glass exhibits excellent soft magnetic properties as well. Large free volume and high structural disorder degree lead to the high toughness.